2021
DOI: 10.15858/engtea.76.s1.202109.37
|View full text |Cite
|
Sign up to set email alerts
|

Motivational Regulation for Learning English Writing Through Zoom in an English-Medium Instruction Context

Abstract: assume responsibility for the same. In addition, the literary works provided by DBpia may only be used by the users affiliated to the institutions which executed a subscription agreement with DBpia or the individual purchasers of the literary work(s)for non-commercial purposes. Therefore, any person who illegally uses the literary works provided by DBpia by means of reproduction or transmission shall assume civil and criminal responsibility according to applicable laws and regulations. 울산과학기술원 114.70.7.*** 202… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…In a recent study of Korean EFL learners' motivational regulation in a ZOOM writing class, J. Kim and V. Kim (2021) investigated how learners manifest their motivational regulation strategies in accordance with their perceptions of the imminent learning context. They found that the high proficiency group valued the synchronous online platform and the university-wide policy of English-medium instruction (EMI) significantly more than the low proficiency group.…”
Section: Situated Learning and Videoconferencementioning
confidence: 99%
See 3 more Smart Citations
“…In a recent study of Korean EFL learners' motivational regulation in a ZOOM writing class, J. Kim and V. Kim (2021) investigated how learners manifest their motivational regulation strategies in accordance with their perceptions of the imminent learning context. They found that the high proficiency group valued the synchronous online platform and the university-wide policy of English-medium instruction (EMI) significantly more than the low proficiency group.…”
Section: Situated Learning and Videoconferencementioning
confidence: 99%
“…The significant correlation between students' use of motivational regulation strategies and their perceptions of contextdependent factors highlighted the importance of situating motivational regulation strategies in a context-specific environment (J. Kim and V. Kim 2021). Further research is still needed which diversifies learner variables in design, such as proficiency levels, and extends the scope to the EFL instructors-their views of the context and learner autonomy.…”
Section: Situated Learning and Videoconferencementioning
confidence: 99%
See 2 more Smart Citations
“…Recently, many scholars (see Lamb, 2017;Nguyen, 2022;Roshandel et al, 2018) have argued that motivation is one of the factors increasing individuals' achievements. Therefore, it could be classified that motivation is one of the foremost disciplines of target language acquirement (Huhtala & Kursisa, 2019; Journal on English as a Foreign Language, 13(1), 218-241 p-ISSN 2088-1657; e-ISSN 2502-6615 Kim & Kim, 2021;Ling-Xia, 2019;Oz & Bursali, 2018;Setiyadi et al, 2019). Additionally, motive learning and accomplishment are objects that could not be parted.…”
Section: Introductionmentioning
confidence: 99%